Regreening properties of the soil slow-mobile H2bpcd/Fe3+ complex: Steps forward to the development of a new environmentally friendly Fe fertilizer - Piccinelli, Fabio; Sega, Davide; Melchior, Andrea; Ruggieri, Silvia; Sanadar, Martina; Varanini, Zeno; Zamboni, Anita (Frontiers in Plant Science, 2022)
The application of synthetic Fe chelates stands for the most established agronomical practice to alleviate lime-induced chlorosis, which still constitutes a major agronomic problem. However, the percolation through the soil profile due to the negative charge of the most deployed molecules results in agronomical and environmental problems. H2bpcd/Fe3+ complex features distinctive chemical characteristics, including moderate stability of the Fe(bpcd)+ species (logML = 20.86) and a total positive charge, we studied its behaviour in soil and regreening effects on cucumber plants. Soil column experiments have underlined that H2bpcd/Fe3+ is much more retained than EDDHA/Fe3+. The new ligand proved not to be toxic for cucumber and maize seedlings. A concentration of 20 μM H2bpcd/Fe3+ attained regreening of Fe-deficient cucumber plants grown in hydroponic solution supplied with CaCO3, as well as EDDHA/Fe3+ did. Experiments with 2 μM of 57Fe showed that cucumber roots absorbed H2bpcd/57Fe3+ at a slower rate than EDTA/57Fe3+. The high kinetic inertness of H2bpcd/Fe3+ may explain such behaviour.